Studi kelayakan bisnis bank pembiayaan rakyat syariah lantabur tebuireng - Fitri, Anis Zakiyah (Maliki Interdisciplinary Journal, 2025)
This article on feasibility study of BPRS (Bank Pembiayaan Rakyat Syariah) Lantabur Tebuireng aims to evaluate the likelihood of success of this Islamic bank in providing financial services based on sharia principles in the region. This feasibility study will cover various aspects, such as market conditions, internal strengths and weaknesses of the bank, as well as potential risks that the bank may face in its operations. It will also cover the risks that may threaten its operations and provide recommendations that are useful for decision makers and relevant stakeholders in planning further development. Through this analysis, it can be concluded that the bank has excellent potential to expand in the Islamic finance market, especially in areas with very strong micro and small economy characteristics. With the implementation of appropriate and sustainable strategies, the bank can not only fulfill the financial needs of the local community, but also has a great opportunity to grow into a trusted Islamic financial institution that contributes positively to the local and national economy.